Density Functional‐Based Tight‐Binding Simulations of Pristine and Aluminum‐Modified Silica. Issue 10 (13th July 2022) - Dernov, Andrei; Tong, Zhen; Kumar, Ravi; Agarwal, Pulkit; Frauenheim, Thomas; Dumitrică, Traian
Abstract: Using self‐consistent density functional tight‐binding simulations it is shown that Aluminum (Al) content in amorphous silica ( a ‐SiO2 ) changes its ideal microscopic structure in a manner compatible to densification. Similar to the structure of pressure‐densified a ‐SiO2, the Al‐modified a ‐SiO2 comprises a network of Silicon (Si)‐centered tetrahedra as well as unquenchable pentahedra and, to a smaller extent, hexahedra coordination defects. Al itself acts not only as a network former, with fourfold coordination, but also as a center for fivefold and sixfold coordination defects. Al content promotes densification since it shifts the potential energy minima at densities larger than in their pristine counterpart. Calculations uncover that Young's modulus ( Y ) and static dielectric constants ( ε 0 ) can be effectively doubled through densification. Oxygen starvation promotes network polymerization, which further increases Y and ε 0 . However, the small rings formation through Si─Si bonding and presence of undercoordinated Si introduce electronic states in the electronic band gap. The results provide guidance for the bottom‐up design of amorphous silica with tunable microscopic structure and properties desirable for advancing electronic applications. Abstract : Density functional‐based molecular dynamics predicts densification of amorphous silica by Aluminum addition. Aluminum content promotes dense silica‐like fivefold and sixfold coordination defects and shifts the potential energy minima to larger densities than in pristine silica. The Young's modulus and static dielectric constant are effectively doubled through densification. The results may have implications for the bottom‐up design of silica films.